ANALISIS BUKU TEKS ESPS BAHASA INDONESIA KELAS 5 SD/MI - Marijan Al-Alam, Muhammad; Muasyasya, Amelia; Aminah, Siti; Nur Azizah, Assifa; Nopasari, Dewi (Sindoro: Cendikia Pendidikan, 2025)
This study aims to analyze the ESPS Bahasa Indonesia textbook for grade 5 SD/MI based on the aspects of content, presentation, language, and graphics. The research employs a literature study method, involving document analysis of the textbook published by the Center for Book Publishing, Standards, Curriculum, and Assessment of Education. The results of the analysis indicate that this book is highly suitable for use as a learning resource, with a feasibility score of 95.51%. The book meets various important criteria, including alignment with the curriculum, completeness of material, accuracy of facts, and a design that supports the learning process. The organized content design, use of simple language, and relevant illustrations effectively assist students in understanding concepts. Additionally, the variety of learning activities, such as discussions, creative projects, and practice exercises, enriches students' learning experiences. By fulfilling the applicable curriculum feasibility criteria, this book not only supports language skills acquisition but also fosters students' character development. This study recommends this book as one of the primary and effective learning resources for grade 5 SD/MI students. Keywords: textbook, feasibility analysis, Bahasa Indonesia Learning, grade 5 SD/MI